2020
DOI: 10.1038/s41598-020-71988-7
|View full text |Cite
|
Sign up to set email alerts
|

Single-institution case series of pituitary biopsy for suspected germinoma in the pediatric population: diagnostic utility, operative risks, and biopsy approaches

Abstract: Little has been reported on the safety and efficacy of pituitary biopsy in the pediatric population for suspected germinoma. An updated review is needed. Patients who underwent biopsy (endoscopic endonasal vs. open craniotomy) for isolated pituitary stalk thickening were identified. Age, pre- and post-operative endocrine status, surgical approach, length of surgery, estimated blood loss, surgical morbidity, length of ICU stay, total length of stay, and pathology reports were reviewed. Nine patients met inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Although some studies suggested that patients with a pituitary stalk of 6–7 mm receive a pathological examination [ 8 ], whether to perform a surgical biopsy deserves careful weighing. On the one hand, although safe [ 29 ], pituitary biopsy is a difficult operation, especially for a small lesion, clinical diagnosis based on significant tumor size regression after a low dose of irradiation or a short course of chemotherapy is easier to perform. [ 30 , 31 ] On the other hand, partial cases of iGCTs were pathologically diagnosed as hypophysitis [ 10 , 11 , 13 , 17 20 , 24 ] or granuloma disease [ 9 , 15 ] at the initial biopsy due to the immune response of the host to germinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggested that patients with a pituitary stalk of 6–7 mm receive a pathological examination [ 8 ], whether to perform a surgical biopsy deserves careful weighing. On the one hand, although safe [ 29 ], pituitary biopsy is a difficult operation, especially for a small lesion, clinical diagnosis based on significant tumor size regression after a low dose of irradiation or a short course of chemotherapy is easier to perform. [ 30 , 31 ] On the other hand, partial cases of iGCTs were pathologically diagnosed as hypophysitis [ 10 , 11 , 13 , 17 20 , 24 ] or granuloma disease [ 9 , 15 ] at the initial biopsy due to the immune response of the host to germinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The study included 91 patients with available histologic diagnosis, of which 92% were pure germinomas and germinomas with syncytiotrophoblastic giant cells, concluding that a tumour biopsy is recommended to ensure the proper diagnosis [ 69 ]. Another retrospective study revealed that in cases of pituitary germinoma suspected on MRI, the biopsy can reveal another pathology in 22% of the tumours [ 70 ]. Moreover, a fairly recent technique that combines endoscopic biopsy with endoscopic ventriculostomy, using a single trajectory, is considered safe and could become an alternative for the dual procedure in pineal germinomas [ 71 ].…”
Section: Diagnosismentioning
confidence: 99%
“…It is well-known that early discrimination of germinomas from other intracranial neoplasms facilitates the timely initiation of appropriate treatment, thereby contributing to the reduction of morbidity as well as mortality. To this effect, a histological confirmation of germinomas by stereotactic or endoscopic biopsy may be necessary [ 13 ]. Additionally, late side effects of the radiotherapy have attracted increasing attention in recent decades due to the consequently high survival rate [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%